Storytelling in Political Communication on Social Media Instagram - Arifuddin, Syafri; Risal, Syamsu; Sukmarini, Andi Vita (Journal La Sociale, 2023)
In two consecutive legislative elections, a candidate was successfully elected by using social media communication methods and abandoning conventional communication patterns. This study aims to understand and analyze the communication methods of the political figure H. Ismail Bachtiar, S.KM., MM on Instagram. The study examines the Instagram account of H. Ismail Bachtiar, S.KM., MM as a channel for political communication. This research uses a qualitative approach with a case study method. Data were collected through interviews, observations, documentation, note-taking, and transcription of content posted on Instagram during the candidacy period of H. Ismail Bachtiar, S.KM., MM as a Legislative Candidate for the DPR RI. This study analyzes the role of storytelling style in communication using the copywriting and rhetorical theories. The findings indicate the political actor's proficiency in expressing ideas, thoughts, and political visions through rhetoric and in crafting personal narratives with a storytelling style to enhance engagement, shape self-image, and build a strong personal identity. The study recommends that political actors further enhance narrative content about prominent figures and their thoughts to inspire young people to enter the political arena.